Optimization of microwave-assisted extraction, antioxidant capacity, and characterization of total flavonoids from the leaves of Alpinia oxyphylla Miq. Issue 1 (2nd January 2020) - Niu, Qing; Gao, Yumei; Liu, Pinghuai
Abstract: To optimize the extraction of total flavonoids (TFL) from the leaves of Alpinia oxyphylla Miq. using microwave-assisted method, a orthogonal test was used. The optimal extraction conditions for TFL were determined as follows: ethanol concentration of 50%, solid–liquid ratio of 1:20, temperature of 70 °C, and cycle index of 3. Under these conditions, the extraction yield of TFL was 28.24%. The scavenging rate of TFL against a, a-diphenyl-b-picrylhydrazyl (DPPH), 2, 2-azino-bis(3-ethylbenzoth- iazoline-6-sulphonica cid) (ABTS), and superoxide anion radical (O2 －· ) was screened. The results showed that the bioactivity of extracts appeared to be TFL dose-dependent, while it also presented stronger ferric reducing antioxidant power (FRAP). The contents of chrysin and tectochrysin in TFL were quantitatively analyzed by HPLC.